Evaluation of proprioception and postural control at a minimum 1 year follow-up after ankle capsuloligamentous lateralplasty with Brostrom technique: A cohort study. Issue 17 (April 2020) - Mosca, Massimiliano; Caravelli, Silvio; Massimi, Simone; Fuiano, Mario; Catanese, Giuseppe; Barone, Giuseppe; Bragonzoni, Laura; Benedetti, Maria Grazia
Abstract : Abstract: Recovery of postural control and proprioception in patients affected by chronic ankle instability (CAI) and operated on capsulo-ligaments reconstructive surgery lacks of objective assessment. The aim of this study was to evaluate long-term post-surgical postural and proprioceptive control through the DPPS device in a cohort of patients operated on ligaments reconstruction through the modified Brostrom procedure at a minimum follow up of 12 months. Eleven patients with post-traumatic lateral CAI, operated of external capsulo-ligamentous complex repair according to Brostrom technique at a minimum follow-up of 1 year were enrolled. Physical examination and American Orthopaedics Foot and Ankle Society (AOFAS) ankle-hindfoot score. Proprioceptive and postural stability was assessed by DPPS - Delos Postural Proprioceptive System, linked to a computer with a specific software and including a flat table, an electronic unstable proprioceptive board, a Delos Vertical Controller, a monitor and a horizontal bar fitted with an infra-red sensor for hand support. Patients were 5 males and 6 females, mean age of 38.4 ± 12 years. Mean BMI of the patients was 26.8 ± 4.4. Mean follow up was 13.4 ± 2.1. The mean value of (AOFAS) clinical score was 90.3/100. Mean Static Stability Index (SSI) with open eyes was 87.7% (±7.6) in the operated leg and 90.4% (±6.1) in the contra-lateral. SSI with closed eyes was 64.5% (±11.2) in the operated leg and 61.6% (±16.8) in the contra-lateral. Mean Dynamic Stability Index (DSI) without restrictions was 56.2% (±14.6) in the operated leg and 56.8% (±10.6) in the contra-lateral. DSI with restricted upper limbs, had a mean value of 56.3% (±11.4) in the operated leg and 58.1% (±11.9) in the contra-lateral. Re-tensioning capsular-ligamentous surgery of the external compartment for CAI allow to recovery proprioceptive and postural control on the operated side, comparable with data from the contralateral limb and from the healthy population of the same age and sex.